Pendidikan keluarga dan anak: Implikasi pengembangan kurikulum bagi keluarga muda - Devina Margaretha Febrianti; Ahmad Ridwan; Agus Machfud Fauzi (Curricula: Journal of Curriculum Development, 2026)
The rapid development of digital technology has transformed the educational landscape within families, necessitating parenting adaptations that account for children's characteristics as digital natives. This study aims to analyze the strategies employed by young families to educate children in the digital era and to examine their implications for the development of the elementary education curriculum. This research was conducted in response to the urgent need to mitigate digital risks, such as gadget addiction and reduced social interaction, given the lack of strong integration between home parenting practices and formal school curricula. The research employed a descriptive qualitative method with purposive sampling, in which data were collected through in-depth interviews, participatory observation, and documentation, and then analyzed thematically. The research findings reveal four dominant strategy patterns: time regulation, content supervision, dialogical communication, and supplementary approaches. Dialogical communication proved to be the most effective in building children's intrinsic awareness, while content supervision supported the educational function of gadgets. These results imply the need to integrate parenting strategies into the elementary school curriculum to create an adaptive educational synergy.